Potential UV (Ultra Violete) Plastic Shade in Increasing Soil Fertility and Controlling Whitefly Pest in Dry Land - Husni, Ika Rauhul; Fauzi, Taufik; Suwardji, Suwardji; Sudharmawan, A. A. Ketut; Mulyati, Mulyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The whitefly is a pest that frequently infests cultivated plants, causing both direct and indirect damage that can significantly reduce crop yields. In addition to whitefly infestations, declining soil fertility is another factor that can lead to decreased production. One potential solution to these issues is the use of UV plastic shade. This method can help reduce the population of whitefly pests. This article aims to explore the effectiveness of UV plastic shade in enhancing soil fertility and reducing whitefly presence in arid regions. The research methodology employed is descriptive, utilizing a literature review of sources such as scientific articles, books, journals, discussions, and previous research findings. UV plastic shade has been found to increase the availability of nitrogen and phosphorus in the soil, thereby promoting soil fertility and plant growth. Additionally, UV plastic shade can reduce whitefly populations in dry areas by disrupting their life cycle and behavior.